Migration in the Enlarged European Union: Empirical Evidence for Labour Mobility in the Baltic States - d'Artis Kancs; Julda Kielyte (Economics and Econometrics Research Institute (EERI), 2002)
The free movement of workers is a highly controversial issue with regard to the Eastern enlargement of the European Union (EU). Members of the EU are extremely anxious of mass immigration flows from Central and Eastern Europe countries (CEECs). This paper estimates the potential migration and analyses socio-economic impacts of migration in the context of the EU enlargement. How many people might migrate from the Eastern European transition countries to Western Europe, and what will be the socio-economic consequences for home and host countries? In order to answer these questions we draw on previous literature as well as on our empirical work. In the empirical analysis we evaluate the size and the structure of current and future migration to Western Europe. In particular, we estimate the future migration pressure, based on economic conditions in the Baltic States and Western Europe. Our empirical results suggest that depending on assumptions 3-5 percent of home countries working population might emigrate after opening labour markets in the old EU member states.
Keywords: F12; F22; L11; 330; International labour migration; EU integration; panel data; econometric model